Quality of Service (QoS) Analysis of the Internet Network at Diskominfo Bengkayang Regency - Sari, Maya; Cahyaningtyas, Christian; Nurcahyo, Azriel Christian (Institut Teknologi Nasional, Bandung, 2025)
The rapid growth in internet usage in recent years has placed significant demands on network service quality. Technological developments and increasingly complex communication needs have made it important to improve the Quality of Service (QoS) of internet networks at Diskominfo Bengkayang Regency. Optimal Quality of Service is essential to support critical applicationssuch as video conferencing, streaming, and other real-time applications. Obstacles such as high latency, low throughput, and lack of prioritization in traffic management can hinder the user experience and reduce service effectiveness. By optimizing QoS, not only does it ensure that critical services receive the appropriate priority, but it also improves the overall efficiency of network resource usage. The involvement of this prioritization scheme in the network infrastructure provides a holistic solution, combining a deep understanding of latency, throughput, and prioritization needs. All of this is done in an effort to optimize QoS so that users can enjoy a good experience when using internet access.